Delayed diagnosis of narcolepsy: characterization and impact - Thorpy, Michael J.; Krieger, Ana C. (Sleep medicine, 2014)
•Narcolepsy is a chronic neurologic condition, which frequently has an early onset.•A long delay until diagnosis has been consistently reported in the literature.•Studies report a mean delay of up to 15years, with individual cases of >60years.•The underlying reason for diagnosis delay is likely a lack of symptom recognition.•We highlight closing this diagnostic gap through awareness of narcolepsy symptoms. Narcolepsy, a chronic neurologic condition resulting from dysregulation of the sleep–wake cycle, usually has an onset at an early age. However, a long delay until diagnosis has been consistently reported in the literature across countries and several publications have focused on characterizing this delay. Most studies report a mean delay to diagnosis of up to 15years, with individual cases of >60years, although a trend over time toward a shorter diagnostic delay has been suggested. While variables associated with this delay have been identified, a lack of symptom recognition resulting in misdiagnosis prior to reaching the narcolepsy diagnosis is the likely underlying reason. This lack of symptom recognition is especially relevant considering the high comorbidity burden that has been shown in patients with narcolepsy as some disorders manifest with symptoms that overlap with narcolepsy. A consequence of delayed diagnosis is delayed treatment, which affects the burden of disease. Substantial detrimental effects on health-care resource utilization, employment, and quality of life have been described after narcolepsy onset and prior to the diagnosis of narcolepsy. This review highlights the importance of closing the diagnostic gap by expanding awareness of narcolepsy and its symptoms.